2017
DOI: 10.1128/iai.00053-17
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Importance of Mast Cells, Basophils, IgE, and IgG versus That of CD4+T Cells and ILC2 Cells in Primary and Secondary Immunity to Strongyloides venezuelensis

Abstract: There is evidence that mast cells, basophils, and IgE can contribute to immune responses to parasites; however, the relative levels of importance of these effector elements in parasite immunity are not fully understood. Previous work in Il3-deficient and c-kit mutant Kit W/W-v mice indicated that interleukin-3 and c-Kit contribute to expulsion of the intestinal nematode Strongyloides venezuelensis during primary infection. Our findings in mast cell-deficient Kit W-sh/W-sh mice and two types of mast cell-defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 76 publications
(97 reference statements)
2
47
0
2
Order By: Relevance
“…Indeed, the last years have witnessed unprecedented progress in our understanding of the development of mast cells [40][41][42]. Moreover, extraordinary progress has been made in understanding the complex homeostatic and protective roles of these cells in different pathophysiological conditions [31,39,114,115]. Mast cells, known for decades for their detrimental role in allergic diseases, are now recognized to play crucial roles in a diverse array of physiological and pathologic functions [15,30,116].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the last years have witnessed unprecedented progress in our understanding of the development of mast cells [40][41][42]. Moreover, extraordinary progress has been made in understanding the complex homeostatic and protective roles of these cells in different pathophysiological conditions [31,39,114,115]. Mast cells, known for decades for their detrimental role in allergic diseases, are now recognized to play crucial roles in a diverse array of physiological and pathologic functions [15,30,116].…”
Section: Discussionmentioning
confidence: 99%
“…For several decades mast cells were considered to play mainly proinflammatory roles in several allergic disorders, such as bronchial asthma [2][3][4]122], allergic rhinitis [5], urticaria [6,7], food allergy [8,9], anaphylaxis [10,11], atopic dermatitis [12], and angioedema [13]. During the last years, it became evident that mast cells represent an important cell during bacterial [26,27,29], fungal [29], viral [25,29], and helminth infections [30,31]. Elegant studies have demonstrated that mast cell-derived mediators can play protective roles against several venoms [114,115].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mast cells employ the same strategy to confer protection against helminth parasites . In fact, IgE‐mediated mast cell induction of type 2 innate lymphoid cells is required for parasite control and expulsion . Recent studies have also demonstrated that mast cells play an important role in protection against arthropod and animal venoms.…”
Section: Mast Cellsmentioning
confidence: 99%
“…larvae infect via the skin, and intestinal adult worm load peaks at 6-8 days post infection (p.i.) and is cleared after 10-12 days 22 . We observed that upon S.v.…”
mentioning
confidence: 99%